Children and teenagers who set fires : why they do it and how to help - Foster, Joanna E. (Jessica Kingsley Publishers, 2020)
"This book helps adults to understand firesetting behaviour in children and teens and provides strategies to work with them to address the behaviour. Drawing upon the latest juvenile firesetting research and utilising child development theory to underpin its safety messages, the book explores why young people might set fires in the first place and contextualises firesetting in terms of communication and gaining the attention of carers and other adults. The chapters lay out practical, tried-and-tested steps that professionals and carers can take to address firesetting behaviour, and suggests how to further support any child or teen who sets fires. This includes summaries of the latest evidence-based support strategies and a range of creative activities that can be used in direct work with children and teenagers who set fires, tailored to specific age ranges. Combining expert advice on firesetting behaviour with straightforward practices, this comprehensive book can be used by anyone working with young people to help them intervene and prevent it"--